(untitled) (Perspectivas em Ciência da Informação, 2025)
Access to public information is an essential pillar of democracy, ensuring transparency, citizen participation, and social oversight. This article provides a comparative analysis of the Inter-American Model Laws on Access to Public Information 1.0 (2010) and 2.0 (2020), highlighting the normative and operational advancements introduced in the latest version. The study adopts a qualitative approach, employing a comparative method and relying on documentary analysis of the normative texts of the Organization of American States (OAS), institutional reports, and specialized literature. Content analysis was used to identify patterns, conceptual changes, and regulatory improvements in access to information governance. The results indicate that Model Law 2.0 expanded the scope of transparency, strengthened institutional mechanisms, reinforced proactive disclosure, and incorporated detailed guidelines on records management, digitization, and oversight. Furthermore, it introduced new interpretative principles and stricter criteria for the exceptions regime. The study concludes that despite these advancements, the effectiveness of the regulation depends on its implementation by member states, the strengthening of oversight institutions, and the adoption of policies that ensure the full application of its provisions.